2001
DOI: 10.1002/1097-4628(20010328)79:13<2439::aid-app1051>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation during isothermal crystallization of isotactic polypropylene

Abstract: Cavitation during isothermal crystallization of thin films of isotactic polypropylene was investigated systematically by light microscopy. Cavitation results from the negative pressure buildup due to density change during crystallization in the pockets of melts occluded by impinging spherulites. The morphology of such areas was also studied by SEM. The value of the negative pressure at the moment of cavitation was calculated from the drop of the spherulite growth rate. It was shown that the process of cavitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…In polyethylene, small (a few micrometers in diameter) spherulites grew, so also small weak spots were formed between them and micrometer-sized cavities were not formed during crystallization [5]. The SAXS studies showed that nano-voids were not present in the non-deformed HDPE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In polyethylene, small (a few micrometers in diameter) spherulites grew, so also small weak spots were formed between them and micrometer-sized cavities were not formed during crystallization [5]. The SAXS studies showed that nano-voids were not present in the non-deformed HDPE.…”
Section: Discussionmentioning
confidence: 99%
“…The SEM photographs showed that weak spots were not very frequent. Nowacki et al [5] observed that the negative pressure buildup was slower in large weak spots formed in polypropylene specimens crystallized at the highest temperatures. The reason was some relaxation of stretched molecules possible during long crystallization and the reduced viscosity of melt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile the rigid conductive network blocked the motion of molecular and internal stress arose, and resulted in a damage of conductive network. Furthermore, the density of crystal was greater than that of amorphous region, and the growing of spherulites caused local volume deficiencies and negative press which leaded to a damage of conductive network [9][10][11]. During the terminal stage of crystallization, conductive network was compacted by the further growing of spherulite and volume resistivity of all samples decreased before its steady [12,13].…”
Section: Resultsmentioning
confidence: 99%